218 - ROUTES OF TRANSMISSION OF TRYPANOSOMA CRUZI IN BRAZIL (Fiep Bulletin - online, 2011)
Chagas disease is one of the most important endemic diseases in Brazil and Latin America, whose causative agent is Trypanosoma cruzi. Within this context, the objectives of this study was to research and discuss the main routes of transmission of the disease and its epidemiology. The classic form of transmission is via a vector, corresponding to 80% of cases of the disease, the main insect vectors to the order Hemiptera, the subfamily Triatominae. In endemic areas treated with chemical control and improve housing, there is reduction and elimination cycle arrest. In the case of man, transmission of T. cruzi occurs orally through food contaminated with the parasite. Today is one of the most important and permanent mechanisms of outbreaks of micro-epidemics in Brazil. In the North, in 2007, Chagas disease has a number of casualties associated with consumption of food, especially the açaí. The main mode of transmission of Chagas disease in urban areas is through transfusion of contaminated blood, the risk is 20%, recent cases have been rare and difficult to detect. The way disease is one in which the T. cruzi can be transmitted through the placenta during pregnancy, can occur at any time, including during delivery. Thus, it is found that in Brazil is less and less significant the incidence of Chagas disease, especially because of the continued control of triatomines resident and rigorous selection of blood donors, combined with the facts emptying demographic and modernization of rural areas. It is expected that it is confined to possible cases of congenital transmission and sporadic cases of congenital transmission or orally in areas under surveillance and wild environments.
Keywords: T; cruzi; Chagas disease; transmission